Length-weight relationships and condition factors of the sand smelt Atherina boyeri (Risso, 1810) estimated from commercial and experimental catches in Lake Trichonis (Western Greece) - Douligeri, Alexandra (Array, 2021)
Total length-weight relationships (LWRs) from 3583 individuals of Atherina boyeri (Risso, 1810) caught in Lake Trichonis (Western Greece), using a commercial encircled net and experimental Nordic type benthic and pelagic multi-mesh gillnets, were estimated during 2019-2020. The variation of the parameter b for all seasons combined was significantly allometric, for both encircled towed and gillnets, with a quite robust fit (R 2 equals 0.925 and 0.947, respectively) and values equal to 2.254 and 2.089, respectively. The specimens were significantly lighter in summer than in the other seasons. The slopes of the LWRs significantly differ between seasons and exhibited relatively low values when compared to other ecosystems worldwide and in the same ecosystem in previous periods of time. Τhe estimated values of the Le Cren index were significantly higher than the Allometric and the Fulton ones.